Evaluasi Kualitas Layanan Learning Management System (LMS) pada Education Priority Menggunakan Metode SERVQUAL - Mellisa Suryani; Siti Aminah; Shinta Aprilisa (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2026)
The use of information technology–based learning systems has increasingly developed and become an important part of supporting the learning process. The Learning Management System (LMS) used at Education Priority serves as the main platform for learning activities and learning evaluation. Therefore, it is necessary to evaluate the service quality of the system to determine the level of conformity between the services provided and user expectations. This study employed a quantitative approach with a descriptive method by distributing questionnaires to 172 LMS user respondents. The research instrument was developed based on the five Servqual dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The analysis was conducted by comparing perception and expectation scores and calculating the gap values. The results indicate that the LMS service quality has not fully met user expectations, with an average gap value of -0.0505. The Reliability dimension has the largest gap (-0.09), while the Empathy dimension has the smallest gap (-0.01).